Urinary Tract Effects of HPSE2 Mutations - Stuart, H (2016)
Urofacial syndrome (UFS) is an autosomal recessive congenital disease featuring grimacing and incomplete bladder emptying. Mutations of HPSE2, encoding heparanase 2, a heparanase 1 inhibitor, occur in UFS, but knowledge about the HPSE2 mutation spectrum is limited. Here, seven UFS kindreds with HPSE2 mutations are presented, including one with deleted asparagine 254, suggesting a role for this amino acid, which is conserved in vertebrate orthologs. HPSE2 mutations were absent in 23 non-neurogenic neurogenic bladder probands and, of 439 families with nonsyndromic vesicoureteric reflux, only one carried a putative pathogenic HPSE2 variant. Homozygous Hpse2 mutant mouse bladders contained urine more often than did wild-type organs, phenocopying human UFS. Pelvic ganglia neural cell bodies contained heparanase 1, heparanase 2, and leucine-rich repeats and immunoglobulin-like domains-2 (LRIG2), which is mutated in certain UFS families. In conclusion, heparanase 2 is an autonomic neural protein implicated in bladder emptying, but HPSE2 variants are uncommon in urinary diseases resembling UFS.